ANALISIS YURIDIS PELAKSANAAN KOMPENSASI TERHADAP KORBAN TERORISME DITINJAU DALAM PERSPEKTIF KEADILAN DISTRIBUTIF - Eva Wardatul Maksufah; Rahtami Susanti (Collegium Studiosum Journal, 2024)
Bom Bali I is one of the terrorist incidents that occurred in Indonesia. Government Regulation in Lieu of Law (Perppu) Number 1 of 2002 and Perppu Number 2 of 2002, which relate to the enactment of Perppu Number 1 of 2002, were subsequently issued as a result of the terrorist incident known as the Bali Bombing. The Minister in Charge of Political, Legal, and Security Matters asked the House of Representatives to amend Government Regulation in Lieu of Law (Perppu) Number 1 of 2002 into Law Number 15 of 2003, but terrorist attacks persisted until President Joko Widodo changed it into Law Number 5 of 2018 concerning the Amendment of the Previous Law. Terrorism causes significant losses, so the government is responsible for protecting victims and fulfilling their rights among which is by offering compensation. Chapter VI of Law Number 5 of 2018 on Law Number 15 of 2003 Amendments regulates the protection of terrorism victims, including information on the payment of compensation of damages to terrorist victims, ranging from economic losses, disabilities, to death. This research uses the Normative Juridical method by analyzing laws, legal documents, and other materials related to the implementation of compensation. Regulations governing the rights of victims have begun to take into consideration the protection of terrorist victims' rights. The government established the National Counter-Terrorism Agency and the Witness and Victim Protection Agency to protect and defend the rights of terrorist victims as intermediaries. The amount of terrorist compensation is also decided by the extent of the victim's loss; in this instance victims' rights terrorism crimes are fulfilled through the interdependence of justice, legal protection, and legal certainty.